HIV-1 transmission and survival according to feeding options in infants born to HIV-infected women in Yaoundé, Cameroon - Anne Esther Njom Nlend; Annie Carole Nga Motaze; Arsene Sandie; Joseph Fokam (BMC, 2018)
Abstract Background Evidence of 24-months survival in the frame of prevention of mother-to-child transmission (PMTCT) cascade-care is scare from routine programs in sub-Saharan African (SSA) settings. Specifically, data on infant outcomes according to feeding options remain largely unknown by month-24, thus limiting its breath for public-health recommendations toward eliminating new pediatric HIV-1 infections and improving care. We sought to evaluate HIV-1 vertical transmission and infant survival rates according to feeding options. Methods A retrospective cohort-study conducted in Yaounde from April 2008 through December 2013 among 1086 infants born to HIV-infected women and followed-up throughout the PMTCT cascade-care until 24-months. Infants with documented feeding option during their first 3 months of life (408 on Exclusive Breastfeeding [EBF], 663 Exclusive Replacement feeding [ERF], 15 mixed feeding [MF]) and known HIV-status were enrolled. HIV-1 vertical transmission, survival and feeding options were analyzed using Kaplan Meier Survival Estimate, Cox model and Schoenfeld residuals tests, at 5% statistical significance. Results Overall HIV-1 vertical transmission was 3.59% (39), and varied by feeding options: EBF (2.70%), ERF (3.77%), MF (20%), p = 0.002; without significance between EBF and ERF (p = 0.34). As expected, HIV-1 transmission also varied with PMTCT-interventions: 1.7% (10/566) from ART-group, 1.9% (8/411) from AZT-group, and 19.2% (21/109) from ARV-naïve group, p < 0.0001. Overall mortality was 2.58% (28), higher in HIV-infected (10.25%) vs. uninfected (2.29%) infants (p = 0.016); with a survival cumulative probability of 89.3% [79.9%-99.8%] vs. 96.4% [94.8%-97.9% respectively], p = 0.024. Mortality also varied by feeding option: ERF (2.41%), EBF (2.45%), MF (13.33%), p = 0.03; with a survival cumulative probability of 96% [94%-98%] in ERF, 96.4% [94.1%-98.8%] in EBF, and 86.67% [71.06%-100%] in MF, p = 0.04. Using Schoenfeld residuals test, only HIV status was a predictor of survival at 24 months (hazard ratio 0.23 [0.072-0.72], p = 0.01). Conclusion Besides using ART for PMTCT-interventions, practice of MF also drives HIV-1 vertical transmission and mortality among HIV-infected children. Thus, throughout PMTCT option B+ cascade-care, continuous counseling on safer feeding options would to further eliminating new MTCT, optimizing response to care, and improving the life expectancy of these children in high-priority countries.